2016
DOI: 10.1039/c6cp04758k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity effects in iron polypyridyl complex electrocatalysis within Nafion thin-film electrodes

Abstract: Four polypyridyl redox catalysts Fe(bp)3(2+), Fe(ph)3(2+), Fe(dm)3(2+), and Fe(tm)3(2+) (with bp, ph, dm, and tm representing 2,2'-bipyridine, 1,10-phenanthroline, 4,4'-dimethyl-2,2'-bipyridine, and 3,4,7,8-tetramethyl-1,10-phenanthroline, respectively) are investigated for the electrocatalytic oxidation of three analytes (nitrite, arsenite, and isoniazid). The poly-pyridyl iron complex is exchanged into a Nafion film immobilized on a glassy carbon electrode, which is then immersed in 0.1 M Na2SO4. Cyclic volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The electrode potential is also affected by the hydrogel where the redox complex is sorbed. Azad et al [64], has proposed that the anionic nature of the polymer matrix (Nafion 1 in their work) decrease the redox potentials of different iron complexes (including TPFeII), compared with solution, through a better stabilization of the more cationic iron(III) species. In this work, we observe lower redox potentials for TPFeII@PAMPS and TPFeII@PAA-co-PAMPS than those measured for TPFeII in solution.…”
Section: Digital Simulation For Evaluation Of Electrochemical Parametersmentioning
confidence: 99%
“…The electrode potential is also affected by the hydrogel where the redox complex is sorbed. Azad et al [64], has proposed that the anionic nature of the polymer matrix (Nafion 1 in their work) decrease the redox potentials of different iron complexes (including TPFeII), compared with solution, through a better stabilization of the more cationic iron(III) species. In this work, we observe lower redox potentials for TPFeII@PAMPS and TPFeII@PAA-co-PAMPS than those measured for TPFeII in solution.…”
Section: Digital Simulation For Evaluation Of Electrochemical Parametersmentioning
confidence: 99%
“…31,32 The negatively charged channels allow permanent uptake and conduction of guest molecules, in particular hydrophobic cations. 33,34 Figure 1. Molecular structure of Nafion ® and schematic representation of the cation (C + ) transport channel formed via selfassembly.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 The negatively charged channels allow permanent uptake and conduction of guest molecules, in particular hydrophobic cations. 33,34 In this report, Nafion is applied as a thin (approximately 5 μm thick) film onto a microhole in a poly ethyleneterephthalate (PET) substrate. The voltammetric characteristics of the resulting "asymmetric" device are compared to the corresponding "symmetric" case with Nafion applied to both sides of the PET substrate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of highly negatively charged anions such as phosphate and arsenate into a semi-permeable ionomer material such as Nafion [38] would usually be ruled out. However, recently, it has been shown that the negatively charged channels of Nafion can be pre-filled for example with cationic iron complexes to result in a binding and sensor function even for anions including arsenite [39]. The cationic species immobilised in the negatively charged ion channel can balance out charges and effectively open the Nafion ion channels to anions.…”
Section: Introductionmentioning
confidence: 99%